2008
DOI: 10.1007/s11814-008-0148-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure fluctuations on the heat transfer characteristics in a pressurized slurry bubble column

Abstract: The hydrodynamics and heat transfer characteristics were investigated in a slurry bubble column reactor whose diameter was 0.0508 m (ID) and 1.5 m in height. Effects of gas velocity (0.025-0.1 m/s), pressure (0.1-0.7 MPa), solid concentration (0-20 vol%) and liquid viscosity (1.0-38.0 mPa s) on the hydrodynamics and heat transfer characteristics were examined. The pressure difference fluctuations were analyzed by means of attractor trajectories and correlation dimension to characterize the hydrodynamic behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…In addition, the wake regions could also coalesce with each other whenever bubble coalescence could occur. It has been reported that the bubble rising velocity increases with increasing gas velocity [14][15][16]; thus, the rising velocity of the wake region can also increase with increasing gas velocity, since the rising bubbles are tailed by wakes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the wake regions could also coalesce with each other whenever bubble coalescence could occur. It has been reported that the bubble rising velocity increases with increasing gas velocity [14][15][16]; thus, the rising velocity of the wake region can also increase with increasing gas velocity, since the rising bubbles are tailed by wakes.…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that the bubble frequency decreases but the rising velocity of bubbles increases, with increasing liquid viscosity. These can be due to the fact that the bubble coalescence could increase with increasing liquid viscosity [14][15][16]. Since the buoyancy force acting on the bubbles, which is due to the difference of density between the bubble and slurry phase, increases with increasing bubble size, the rising velocity of wakes as well as bubbles could increase with increasing liquid viscosity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total acquisition time was 10 s having 5000 data points. This combination of sampling rate and time can detect the full spectrum of temperature fluctuation signals in a multiphase flow system [13][14][15][16].…”
Section: May 2010mentioning
confidence: 99%
“…Recently, the multiresolution signal decomposition [6] has been widely applied to analyze pressure fluctuation signals with multiscale features and unsteady characteristics in fluidization and bubble columns in chemical engineering [7][8][9][10][11][12]. Another technique, the chaotic time series analysis, has also shown great advantages in studying the nonlinear dynamics of bubble columns [4,13,14]. In the present work, both the multiresolution signal decomposition and chaotic time series analysis were simultaneously employed to analyze the temporary signals of bubble passages in non-Newtonian fluids and then to characterize qualitatively and quantitatively the nonlinear dynamics of in-line bubbles rising with coalescences.…”
Section: Introductionmentioning
confidence: 99%